2010
DOI: 10.1111/j.1574-6968.2010.01997.x
|View full text |Cite
|
Sign up to set email alerts
|

The unique set of putative membrane-associated anti-σ factors in Clostridium thermocellum suggests a novel extracellular carbohydrate-sensing mechanism involved in gene regulation

Abstract: Genome analysis of the Gram-positive cellulolytic bacterium Clostridium thermocellum revealed the presence of multiple negative regulators of alternative sigma factors. Nine of the deduced proteins share a strong similarity in their N-terminal sequences to the Bacillus subtilis membrane-associated anti-sigma(I) factor RsgI and have an unusual domain organization. In six RsgI-like proteins, the C-terminal sequences contain predicted carbohydrate-binding modules. Three of these modules were overexpressed and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
112
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(120 citation statements)
references
References 38 publications
1
112
0
Order By: Relevance
“…For example, we found that 16 out of the 76 CBMs of C. thermocellum occur independent of GH domains. Some of them are fused with transmembrane domains and anti-sigma factor-like proteins and are proposed to be involved in the regulation of cellulosome expression in C. thermocellum (16), but for most of these non-GH-linked CBMs, including the orphan CBMs from S. thermophila, the functions remain to be unraveled.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we found that 16 out of the 76 CBMs of C. thermocellum occur independent of GH domains. Some of them are fused with transmembrane domains and anti-sigma factor-like proteins and are proposed to be involved in the regulation of cellulosome expression in C. thermocellum (16), but for most of these non-GH-linked CBMs, including the orphan CBMs from S. thermophila, the functions remain to be unraveled.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated negative regulation of noncellulosomal enzymes by GlyR3 transcription factor (11,19). Positive regulation of cellulosome enzymes through cellulose and xylan interactions with anti-factors has been reported (17,20,21). Further studies are required to refine knowledge of C. thermocellum gene-regulatory networks contributing to the control and composition of the cellulosome and the lignocellulolytic abilities of the organism, regulation of important physiological responses, and cross talk between networks.…”
Section: Discussionmentioning
confidence: 98%
“…However, only a small proportion of C. thermocellum transcriptional regulators have been studied. Previous work has demonstrated the inducible expression of the celC-glyR3-licA operon (11,19), the involvement of alternative sigma factors with their cognate anti-sigma factors in the regulation of cellulolytic genes, including celS (17,20,21), and histidine kinase genes involved in the regulation of sporulation (22).…”
mentioning
confidence: 99%
“…Previously, Stevenson and Weimer conducted a real-time PCR survey of the expression of 17 C. thermocellum genes involved in cellulose hydrolysis, intracellular phosphorylation, and catabolite repression and correlated their expression profiles with the formation of fermentation products (31). Most recently, sigma factor signaling in C. thermocellum was established by an elegant combination of bioinformatics and biochemical approaches (17). Collectively, these studies point to the ability of C. thermocellum to exquisitely control expression of certain known genes in response to growth rate and the presence of insoluble cellulose or soluble compounds such as cellobiose.…”
mentioning
confidence: 99%
“…The most highly expressed genes from this set encode glycoside hydrolases, scaffoldins, and other proteins known to participate in cellulose utilization. A large number of transcriptional regulators, signal transduction proteins (34), and sigma factors (17) were also identified, thus expanding our understanding of potential mechanisms of control for clostridial gene expression and protein translation. The expression data also revealed that certain genes among multiple copies from the glycolytic, ethanol fermentation, and H 2 evolution pathways were highly expressed under conditions that led to ethanol production.…”
mentioning
confidence: 99%